Search for ammonia in comet C/2012 S1 (ISON). (1st December 2015) - Faggi, S.; Codella, C.; Tozzi, G.P.; Comoretto, G.; Crovisier, J.; Nesti, R.; Panella, D.; Boissier, J.; Brucato, J.R.; Bolli, P.; Massi, F.; Tofani, G.
Abstract: Comets are uniquely pristine bodies providing unique insights about the formation of our Solar System. In this work, we focus on a dynamically new comet as it enters the inner Solar System for the first time after residing for billion of years in the Oort Cloud. Such comets are particularly important because they are thought to be not differentiated by solar radiation and they are supposed to have a large quantity of organic matter close to the surface. Here we report the results of a search for NH3 (1, 1) emission at 23.7 GHz towards comet C/2012 S1 (ISON) using a new dual-feed K band receiver mounted on the Medicina 32-m antenna. We observed the comet close to its perihelion, from 25 to 29 November 2013, when its heliocentric distance changed from 0.25 AU to 0.03 AU. We derive an upper limit of Q (NH3 ) of about 2.5×10 29  mol s −1 on 26 November, that is consistent with the last peak of water production rate of ∼2×10 30  mol s −1 within the last few days before the perihelion.